2018
DOI: 10.1159/000491956
|View full text |Cite
|
Sign up to set email alerts
|

Mutant MAPK7-Induced Idiopathic Scoliosis is Linked to Impaired Osteogenesis

Abstract: Background/Aims: Three rare MAPK7 variants that predispose individuals to adolescent idiopathic scoliosis have previously been identified. However, the mechanism underlying the effects of the mutations remain unknown. Methods: Human mesenchymal stem cells (hMSCs) were isolated from both patients and healthy volunteer donors, and MAPK7 expression was detected by western blotting and real-time quantitative PCR (RT-qPCR). Zebrafish embryos were injected with mapk7 morpholinos or co-injected with morpholinos and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
(52 reference statements)
0
13
0
1
Order By: Relevance
“…88 More recently, MapK7 was shown to be associated with severe spinal deformity and a defective osteogenesis phenotype in idiopathic scoliosis. 162 Understanding the molecular underpinnings that generate spinal deformities may allow for early targeted therapy based on a child's underlying genetic profile. The development and refinement of new fusionless surgical techniques may allow for early treatment of pediatric patients with high risk of deformity progression without the long-term consequences of current fusion constructs.…”
Section: Fusionless Spine Surgerymentioning
confidence: 99%
“…88 More recently, MapK7 was shown to be associated with severe spinal deformity and a defective osteogenesis phenotype in idiopathic scoliosis. 162 Understanding the molecular underpinnings that generate spinal deformities may allow for early targeted therapy based on a child's underlying genetic profile. The development and refinement of new fusionless surgical techniques may allow for early treatment of pediatric patients with high risk of deformity progression without the long-term consequences of current fusion constructs.…”
Section: Fusionless Spine Surgerymentioning
confidence: 99%
“…In future perspective, it would be highly interesting to investigate how common risk factors affect the disbalance between MAPK7 activity and EZH2 expression in larger cohort studies. In addition, and since polymorphisms in MAPK7 48 50 and EZH2 51 – 54 are identified, it would be highly interesting to investigate whether these polymorphisms associate to a higher cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MAP2K1, which was shown to be down regulated in the expression study, interacts directly with PRKG1, and is involved in cGMP-PKG signaling, as well as MAPK and PI3K-Akt signaling. Mutant MAPK7-induced AIS has been linked to impaired osteogenesis 28 . Previous study has indicated that p38 and MAPK play important roles in the production of collagen in fibroblasts 29 .…”
Section: Discussionmentioning
confidence: 99%